Coronary Angioplasty with a Drug-Coated Balloon Catheter in the Treatment of Acute Coronary Syndromes: Medico-Social Perspectives and Challenges of Use in the Setting of Diffuse Coronary Artery Lesions — A Literature Review - Aksenov, Evgen V.; Hladun, Artem Yu.; Kalashnikov, Sviatoslav A. (Ukrainian Journal of Cardiovascular Surgery, 2025)
This literature review explores the role of drug-coated balloon (DCB) angioplasty in the management of acute coronary syndromes (ACS), with a particular focus on patients with diffuse coronary artery disease. Aim. To conduct a literature review on the benefits of using DCB in the treatment of patients with diffuse coronary artery disease and ACS. Materials and methods. Unlike traditional drug-eluting stents (DES), DCB technology delivers antiproliferative drugs directly to the lesion site without leaving behind a permanent implant, offering significant advantages such as reduced risk of in-stent restenosis (ISR), lower rates of thrombosis, and shorter required durations of dual antiplatelet therapy (DAPT). These benefits are especially relevant in high-risk populations, including elderly patients, those at high risk of bleeding, or those requiring urgent non-cardiac surgery. The review synthesizes data from key randomized controlled trials (PEPCAD NSTEMI, REVELATION, BASKET-SMALL 2), and meta-analyses. Results. The review demonstrates the non-inferiority of DCB compared to DES in terms of major cardiovascular outcomes, even in complex settings, such as ST-elevation myocardial infarction (STEMI) and out-of-hospital cardiac arrest (OOHCA). In addition, DCB has proven effective in treating ISR and preserving endothelial function, with evidence of late lumen enlargement and minimal vascular trauma. However, challenges remain, including the need for precise lesion preparation, proper balloon sizing, and operator expertise. Limitations in long-term data and heterogeneity in patient selection across studies highlight the need for further large-scale trials. Conclusions. DCB angioplasty represents a promising, less invasive strategy in interventional cardiology, particularly in patients with diffuse or high-risk coronary lesions, though widespread adoption will depend on continued research and protocol optimization.